PERBAIKAN DATA DOKUMEN IMPOR TERHADAP ON TIME CLEARANCE PADA PT. DHL GLOBAL FORWARDING INDONESIA - Norman Irhamna; Vannesa Aprilian (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2016)
PT. DHL Global Forwarding is a freight forwarder company, which is engaged in freight forwarding, logistics and deliver exported and imported goods. The problem in this research is the influence of the data repair (redress) to the on-time clearance at PT. DHL Global Forwarding Indonesia in 2015. The purpose of the study was to determine the influence of the data repair (redress) to the clearance on time. To solve this problem, the authors use qualitative methods of Logical Framework Approach (LFA). Authors collected data through observation and interviews to 5 employees as a sampel. By using the LFA analysis, showed that the improvement of data (redress) greatly affect on-time clearance, due to the improvement of data (redress) indicates that the data are subject to rejection or reject so it takes 1-5 days to process correction means exceeds Key Performance Indicator (KPI)